2019
DOI: 10.3389/fphar.2019.00309
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Novelty-Induced Hyperactivity of Gria1-/- Mice by Cannabidiol and Hippocampal Inhibitory Chemogenetics

Abstract: Gene-targeted mice with deficient AMPA receptor GluA1 subunits ( Gria1-/- mice) show robust hyperlocomotion in a novel environment, suggesting them to constitute a model for hyperactivity disorders such as mania, schizophrenia and attention deficit hyperactivity disorder. This behavioral alteration has been associated with increased neuronal activation in the hippocampus, and it can be attenuated by chronic treatment with antimanic drugs, such as lithium, valproic acid, and lamotrigine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
3
9
0
Order By: Relevance
“…This is supported by the large body of evidence demonstrating the control of dopaminergic activity by the vHC and vSub in rodents, and the potential therapeutic effects achieved by local interventions in the vHC [ Tables 1 and 3 , ( Gilani et al, 2014 )]. However, salience-like signals in rodents have mostly been recorded in the dorsal hippocampus which receives predominantly sensory information, and more successful rescue approaches which reduce hippocampal hyperactivity in genetic mouse models of schizophrenia have been conducted in the dorsal subregion ( Marissal et al, 2018 ; Aitta-aho et al, 2019 ; Mukherjee et al, 2019 ) than in the vHC ( Gilani et al, 2014 ). Therefore, further elucidation of the different functional roles of the dorsal and ventral subregions in schizophrenia-related deficits remains a pressing need.…”
Section: Limitations and Challenges Of Harnessing The Hippocampus→nacmentioning
confidence: 99%
“…This is supported by the large body of evidence demonstrating the control of dopaminergic activity by the vHC and vSub in rodents, and the potential therapeutic effects achieved by local interventions in the vHC [ Tables 1 and 3 , ( Gilani et al, 2014 )]. However, salience-like signals in rodents have mostly been recorded in the dorsal hippocampus which receives predominantly sensory information, and more successful rescue approaches which reduce hippocampal hyperactivity in genetic mouse models of schizophrenia have been conducted in the dorsal subregion ( Marissal et al, 2018 ; Aitta-aho et al, 2019 ; Mukherjee et al, 2019 ) than in the vHC ( Gilani et al, 2014 ). Therefore, further elucidation of the different functional roles of the dorsal and ventral subregions in schizophrenia-related deficits remains a pressing need.…”
Section: Limitations and Challenges Of Harnessing The Hippocampus→nacmentioning
confidence: 99%
“…Gainetdinov et al (2001) showed that drugs that enhance glutamatergic transmission, such as positive modulators of L-α-amino-3-hydroxy-5-methylisoxazole-4-propionate glutamate receptors, suppress the hyperactivity of mice lacking the dopamine transporter (Gainetdinov et al, 2001). The involvement of the glutamate system in the development of attention-deficit disorder, hyperactivity, and other behavioral motor disorders has also been previously described (Procaccini et al, 2013;Maksimovic et al, 2014a,b;Miller, 2019;Aitta-Aho et al, 2019). Halberstadt et al (2011) demonstrated that loss of mGlu5 receptor activity either pharmacologically or through gene deletion leads to locomotor hyperactivity in mice.…”
Section: Discussionmentioning
confidence: 84%
“…These mice exhibited mania-like hyperactivity when placed in a novel environment. This hyperactivity was blunted by both systemic and intra-hippocampal administration of CBD (Aitta-aho et al, 2019). Another study, however, failed to find any effect of CBD on locomotor activity in a different model of bipolar mania.…”
Section: Resultsmentioning
confidence: 98%